Horse Tourism Development Strategies in South Tugu Village, Bogor Regency Based on PESTLE and SWOT Analysis - Lucia Cyrilla Eko Nugrohowati Supriyadi Dekrityana; Verika Armansyah Mendrofa; Surya Adinata (Badan Penerbitan Fakultas Pertanian (BPFP), 2026)
South Tugu Village has significant potential to develop a tourism village based on natural beauty and local wisdom. One of its emerging attractions is horse tourism, known as Kampung Koboy. However, sustainable development of this attraction requires a assessment of its potential and the formulation of development strategies. This study aimed to identify the development potential of horse tourism in Kampung Koboy, South Tugu Village, based on political, economic, sociocultural, technological, legal, and environmental aspects. Data were collected through interviews with 34 horse farmers and several community leaders involved in the Kampung Koboy community. The data were analyzed using PESTLE (Political, Economic, Sociocultural, Technological, Legal, and Environmental) and SWOT (Strengths, Weaknesses, Opportunities, and Threats) analyses. The results indicate that Kampung Koboy possesses strong potential for further tourism development. Improvements in technology adoption, human resource capacity, and supporting infrastructure are needed to enhance competitiveness and sustainability. Recommended strategies include organizing tourism activities that emphasize local wisdom, developing racehorse breeding programs, offering affordable private group riding packages, implementing training and certification programs for horse breeders, and encouraging community participation in developing distinctive Kampung Koboy products. These strategies are expected to strengthen tourism attractiveness and ensure long term sustainability in South Tugu Village.